Aerobic Exercise Training-Induced Changes on DNA Methylation in Mild Cognitively Impaired Elderly African Americans: Gene, Exercise, and Memory Study - GEMS-I - Ngwa, Julius S.; Nwulia, Evaristus; Ntekim, Oyonumo; Bedada, Fikru B.; Kwabi-Addo, Bernard; Nadarajah, Sheeba; Johnson, Steven; Southerland, William M.; Kwagyan, John; Obisesan, Thomas O. (Frontiers in Molecular Neuroscience, 2022)
Background: DNA methylation at CpG sites is a vital epigenetic modification of the human genome affecting gene expression, and potentially, health outcomes. However, evidence is just budding on the effects of aerobic exercise-induced adaptation on DNA methylation in older mild cognitively impaired (MCI) African American (AAs). Therefore, we examined the effects of a six-month aerobic exercise-intervention on genome-wide DNA methylation in older AA MCI volunteers. Design: Elderly AA volunteers confirmed MCI assigned into six-month program of aerobic exercise (eleven participants) underwent 40-minute supervised-training 3-times/week and controls (eight participants) performed stretch training. Participants had maximal oxygen consumption (VO2max) test and Genome-wide methylation levels at CpG sites using Infinium HumanMethylation450 BeadChip assay at baseline and six-month exercise program. We computed false discovery rates (FDR) using Sidak to account for multiplicity of tests and performed quantitative real-time polymerase chain-reaction (RT-PCR) to confirm effects of DNA methylations on expression levels of the top 5 genes among the aerobic participants. CpG sites identified from aerobic-exercise participants were similarly analyzed by the stretch group to quantify effects of exercise-induced methylation changes among the group of stretch participants. Results: Eleven MCI participants (aerobic: 73% females; mean age 72.3 ± 6.6 years) and eight MCI participants (stretch: 75% female; mean age 70.6 ± 6.7 years) completed the training. Aerobic exercise-training was associated with increases in VO2max, and with global hypo- and hypermethylation changes. The most notable finding was CpG hypomethylation within the body of the VPS52 gene (P = 5.4 x 10-26), a Golgi-associated protein, involved in intracellular protein trafficking including amyloid precursor protein. RT-PCR confirmed a nearly two-fold increased expression of VPS52. Other top findings with FDR q-value < 10-5, include hypomethylations of SCARB1 (8.8 x 10-25), ARTN (6.1 x 10-25), NR1H2 (2.1 X 10-18) and PPP2R5D (9.8 x 10-18). Conclusion: We conclude that genome-wide DNA methylation patterns is associated with exercise training-induced methylation changes. Identification of methylation changes around genes previously shown to interact with amyloid biology, intracellular protein trafficking, and lipoprotein regulations provide further support to the likely protective effect of exercise in MCI. Future studies in larger samples are needed to confirm our findings.